Economic and Welfare Effects of the Abolition of Health User Fees: Evidence from Uganda - Deininger, Klaus; Mpuga, Paul (World Bank, Washington, D.C., 2013)
The authors use household level data for Uganda for 1999-2000 and 2002-03, before and after the abolition of user fees for public health services, to explore the effect of this policy on different groups' ability to access health services and morbidity outcomes. They find that the policy change improved access and reduced the probability of sickness in a way that was particularly beneficial to the poor. Although the challenge of maintaining service quality remains, aggregate benefits are estimated to be significantly larger than the estimated shortfalls from the abolition of user fees.